Investigating the Effectiveness of Self-Control for Pupils - Reflective Journaling (STOP-RJ) in Enhancing Self-Control Among Juvenile Detainees - Megawati, Hermeilia; Qonita, Adhissa; Maharani, Aisyah; Kurniati, Kurniati; Syahrial, Putri Devrina; Salsabila, Qorri ‘Ainan; Sy, Vinna Ramadhany; Lubis, Irma Rosalinda (Faculty of Psychology, Universitas Gadjah Mada, 2025)
This study investigated the efficacy of Self Control for Pupils - Reflective Journaling (STOP-RJ) intervention program in enhancing self-control among juvenile detainees at the Jakarta Youth Correctional Center (LPKA Jakarta). A total of 15 male juvenile detainees, aged 15 to 18 years (M = 16.73), selected through convenience sampling, participated in the study with the approval of institutional authorities. Over the course of the 15-day program, participants were instructed to maintain reflective journals that focused on two primary aspects of self-control: emotional expression and adaptive social behavior. Their self-control levels were assessed using a self-control scale both before and after the intervention. Data analysis was conducted using a paired sample t-test with the JASP program version 0.16.3.0. The findings revealed a significant increase in adaptive social behavior, accompanied by a large effect size (t (1.15) = 4.141, p < 0.001, d = 1.069). These outcomes reinforce the potential implications of structured reflective exercises in enhancing self-control skills among juvenile detainees.